1997
DOI: 10.1002/(sici)1097-0134(199703)27:3<395::aid-prot7>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Solvent structure at a hydrophobic protein surface

Abstract: The impact of an extensive, uniform and hydrophobic protein surface on the behavior of the surrounding solvent is investigated. In particular, focus is placed on the possible enhancement of the structure of water at the interface, one model for the hydrophobic effect. Solvent residence times and radial distribution functions are analyzed around three types of atomic sites (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 33 publications
7
37
0
Order By: Relevance
“…In harmony with the present work, in several recent studies (35)(36)(37) no clear relationship between first-shell water density variations and the hydrophobicity͞hydrophilicity of chemical groups has been found. Moreover, in the present simulation, although the water oxygen:surface protein atom PCFs in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In harmony with the present work, in several recent studies (35)(36)(37) no clear relationship between first-shell water density variations and the hydrophobicity͞hydrophilicity of chemical groups has been found. Moreover, in the present simulation, although the water oxygen:surface protein atom PCFs in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…B (2004) shell water density and the chemical characteristics of the surface atoms or residues, for example, whether polar/non-polar or hydrophobic/hydrophilic. In agreement with this result, in several recent studies (Finney et al 1993;Pertsemlidis et al 1996;Kovacs et al 1997) no clear relationship between first-shell water density variations and the hydrophobicity/hydrophilicity of chemical groups has been found. The exceptions are groups with net charges, about which the density is increased.…”
Section: Solvent Structure On a Protein Surfacesupporting
confidence: 71%
“…NMR and neutron spectroscopy have revealed altered mobility of water molecules on protein surfaces with respect to the bulk (11)(12)(13)(14)(15), and time-resolved vibrational spectroscopy has revealed distinctive dynamics of solvation near the active sites of enzymes during catalysis with respect to bulk solvent (16). Increased water density in the first hydration shell (HS), as well as surface-specific differences in the organization of the hydration water, have been reported by MD simulations (17)(18)(19)(20) and have been described thermodynamically in terms of electrorestriction (21). MD studies involving nucleic acids (7,22,23) or proteins (24,25), as well as anomalous x-ray solution studies on proteins and nucleic acids (26,27), have revealed the specific recruitment of ions into their HSs.…”
Section: Introductionmentioning
confidence: 95%